Evidence for Inflammation as a Driver of Atrial Fibrillation - Zhou, Xiaoxu; Dudley, Samuel C. (Frontiers in Cardiovascular Medicine, 2020)
Atrial fibrillation (AF) is one of the most common type of arrhythmias and increases cardiovascular morbidity and mortality. Current therapeutic approaches to AF that focus on rhythm control have high recurrence rates and no life prolongation value. While possible explanations include toxicity of current therapies, another likely explanation may be that current therapies do not address fundamental mechanisms of AF initiation and maintenance. Inflammation has been shown to affect signaling pathways that lead to the development of AF. This paper reviews the roles of inflammation in the occurrence, development, and mechanisms of AF and reviews the therapeutic implications of the correlation of inflammation and AF.